2019
DOI: 10.1002/marc.201900059
|View full text |Cite
|
Sign up to set email alerts
|

An Ionomeric Renewable Thermoplastic from Lignin‐Reinforced Rubber

Abstract: An ionomeric, leathery thermoplastic with high mechanical strength is prepared by a new thermal processing method from a soft, melt‐processable rubber. Compositions made by incorporation of equal‐mass lignin, a renewable oligomeric feedstock, in an acrylonitrile‐butadiene rubber often yield weak rubbers with large lignin domains (1–2 µm). The addition of zinc chloride (ZnCl2) in such a composition based on sinapyl alcohol‐rich lignin during a solvent‐free synthesis induces a strong interfacial crosslinking bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…The distribution of different types of crosslinks is affected by the reversion time, and the inclusion of lignin showed that it actually takes part during the vulcanization process and that the mechanism is due to the thermal stability itself. Besides, the conventional vulcanization (CV) system delayed the optimum cure time, but the semi-efficient (semi-EV) and efficient vulcanization (EV) systems increased the cure rate (Nando and De, 1980;Shukla et al, 1998;Kakroodi and Sain, 2016). Nevertheless, some studies reported that the presence of lignin decreased the crosslink density and the number of polysulphidic crosslinks while maintaining the number of disulfidic and monosulfidic crosslinks (Kumaran and De, 1978;Kakroodi and Sain, 2016).…”
Section: Cure Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The distribution of different types of crosslinks is affected by the reversion time, and the inclusion of lignin showed that it actually takes part during the vulcanization process and that the mechanism is due to the thermal stability itself. Besides, the conventional vulcanization (CV) system delayed the optimum cure time, but the semi-efficient (semi-EV) and efficient vulcanization (EV) systems increased the cure rate (Nando and De, 1980;Shukla et al, 1998;Kakroodi and Sain, 2016). Nevertheless, some studies reported that the presence of lignin decreased the crosslink density and the number of polysulphidic crosslinks while maintaining the number of disulfidic and monosulfidic crosslinks (Kumaran and De, 1978;Kakroodi and Sain, 2016).…”
Section: Cure Propertiesmentioning
confidence: 99%
“…Besides, the conventional vulcanization (CV) system delayed the optimum cure time, but the semi-efficient (semi-EV) and efficient vulcanization (EV) systems increased the cure rate (Nando and De, 1980;Shukla et al, 1998;Kakroodi and Sain, 2016). Nevertheless, some studies reported that the presence of lignin decreased the crosslink density and the number of polysulphidic crosslinks while maintaining the number of disulfidic and monosulfidic crosslinks (Kumaran and De, 1978;Kakroodi and Sain, 2016). They suggested that the incorporation of lignin in the rubber matrix masked some of the cross-linking sites on the rubber molecules.…”
Section: Cure Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lai et al reported that the polydimethylsiloxane (PDMS) cross-linked by abundant Zn 2+ –carboxylate interactions was very strong at room temperature and exhibited fast thermal-healing properties . Metal coordination bonds can also undergo reversible rupture and reconstruction under the tensile stress, which effectively dissipates mechanical energy and provides excellent mechanical properties. , Filippidi et al incorporated reversible Fe 3+ -catechol coordination interactions into a lightly cross-linked epoxy network . The tensile strength, toughness, and stiffness of the Fe 3+ -containing network were improved by 2–3 orders of magnitude compared with the Fe 3+ -free network .…”
Section: Introductionmentioning
confidence: 99%